Strategic training and development - Berkley, Robyn A.; Kaplan, David M. (SAGE, 2020)
"Strategic Employee Training and Development by Robyn A. Berkley and David M. Kaplan is designed to provide students with the knowledge and skills necessary to conduct strategic, effective training and development in the workplace. Grounded in research and scholarship, the text offers a strong emphasis on practical skills such as providing feedback, goal-setting, facilitating sessions, and presentations as well as interpersonal skills such as emotional intelligence, self-awareness, active listening, and conflict resolution skills. With a special focus on understanding individual differences, the authors explore how considerations like diversity, culture, personality, values, and learning affect training and development. The text begins by introducing training and development in the context of business strategy and the legal environment. Next, the text covers the foundational elements of training (i.e. needs assessment, training design, learning, partnerships) and training evaluation and transfer. Providing substantial coverage of employee development, Strategic Employee Training and Development addresses often-overlooked topics like succession planning and high-potential employees"